Enhancing MSMEs Financial Resilience: Integrating Working Capital Management and Sustainability Reporting - Hamzah, Ruth Samantha; Gozali, Efva Octavina Donata; Sitepu, Christian Damar Sagara (Universitas Muhammadiyah Semarang, 2024)
This study examines the influence of sustainability reporting (SR) comprehension and working capital management (WCM) on the financial performance of small and medium-sized manufacturing enterprises (MSMEs). Furthermore, the study emphasizes WCM's impact on financial performance, which is linked to understanding SR among MSMEs actors. The study incorporates control variables in the model (e.g., age, size, ownership type, organizational culture, market orientation, entrepreneurial orientation). The sample is selected using quota sampling of MSMEs in the manufacturing sector in Palembang, Indonesia, from October to November 2023. Primary data collection is distributed online through questionnaires. The results show that understanding SR and WCM positively affect the financial performance of MSMEs. The findings deliver several contributions. Firstly, the implementation of SR of MSMEs – in the long term – would benefit the government in supporting sustainable development goals (SDGs). Secondly, it bridges the literature gap regarding the implementation of SR and WCM to examine the performance of MSMEs.